Web Integrated STEM Learning: Effects on Students’ Academic Achievement, Creativity and Metacognitive Awareness - Ayberk Bostan Sarıoğlan; Özge Şentürk Özkaya (Universitas Pendidikan Indonesia, 2023)
This study examines the effect of teaching with the STEM Cycline of the 'Force and Energy' unit on students' creativity, metacognitive awareness, and academic achievement. The nonequivalent control group design, one of the quasi-experimental models, was used in the study. The study included 54 seventh-grade students studying at a public school in western Turkey, 27 of whom were in the experimental group while 27 were in the control group. The experimental group was taught with the STEM Cycline, whereas the control group took the instruction within the science curriculum framework. The experimental group designed models using Web 2.0 tools related to the given problems and used these models to solve them by printing them from a 3D printer.